Antioxidant and hepatoprotective activity of ethanolic and aqueous extracts of Limonia elephantum leaves - K. Kamalakannan; Veluchamy Balakrishnan (Bangladesh Pharmacological Society, 2014)
Limonia elephantum (wood apple) has been widely used in an Indian folk medicine system. In the present study, the acute toxicity studies were carried out to determine the safety of the compounds in liver diseases. The antioxidant and the hepatoprotective properties of the L. elephantum are evaluated against paracetamol induced hepatic damage in rats. Liver superoxide dismutase, lipid peroxidation, glutathione peroxidase, catalase levels and serum biochemical profile such as serum glutamate oxalate transaminase, serum glutamate pyruvate  transaminase, alkaline phosphatase, bilirubin and total protein were examined for the antioxidant and hepatoprotective effects of these treatments. The results of the present studies strongly indicate that the higher dose (400 mg/kg) of ethanolic extract of L. elephantum proved against hepatoprotective effects and also the antioxidant properties.